187 A collaborative scholar retreat model to create dialogue among training programs - Shaweta Singla; Jessica Petrie; Gail Thomas; Stephen Wilson; David Rabago; Marie Boltz; Lauren Van Scoy (Journal of Clinical and Translational Science)
Objectives/Goals: In Fall 2024, we designed a collaborative scholar retreat model to create dialogue among our training programs. The purpose of the retreat was to foster collaboration and provide unique networking opportunity for our KL2, T32, and TL1 scholars to share their research across the translational spectrum and learn more about Clinical and Translational Science Institute (CTSI) resources and tools. Methods/Study Population: The CTSI Fall Scholar Retreat brought together a diverse group of 25 scholars who attended in-person a full-day program. The program included presentations on CTSI resources and Team Science on How to Become a Better Team Member in cross-disciplinary and cross-functional groups. The KL2 Scholars presented motivational talks on their career and professional development journeys. Mentoring roundtable included discussions on subthemes like characteristics of a good mentor/mentee, organizing your mentoring team, different mentor roles, and fears of approaching new mentor/mentee. TL1 and T32 scholars also presented posters describing their ongoing research project from the planning stages to initial observations to completed studies. Results/Anticipated Results: To measure the effectiveness and impact of the CTSI Fall Scholar Retreat, we conducted an evaluation using REDCap survey and received an 88% response rate. On the Likert scale of 1–5 (1 = not at all valuable, 2 = not very valuable, 3 = neutral, 4 = very valuable, and 5 = extremely valuable), 92% of the scholars found the sessions to be valuable. Net Promoter Score of 9.6 (scale of 1–10) was measured to collect the scholar feedback and most of them are likely to recommend the Scholar Retreat to other scholars. Discussion/Significance of Impact: The in-person retreat proved to be a unique platform to interact, collaborate, learn, and grow for all scholars at different levels of their career and research. Inclusion of HRSA-funded T32 post-doctoral program provided cross-level collaboration and helped promote a culture of continuous learning in clinical and translational science.